Article 6.8 | CGIAR Road from COP29 to COP30Webinar Series #1 - CGIAR Science Program on Climate Action (2025)
Significant progress was made at COP29 in Baku under Article 6 of the Paris Agreement, particularly with the advancements in the operationalization of Article 6.8, which supports non-market mechanisms (NMAs). These developments are expected to enhance international cooperation on mitigation and adaptation, providing countries with additional tools to meet their climate commitments effectively.